Analysis of pseudoscientific texts from the Psychology students’ epistemic beliefs - Meza Cano, José Manuel; Salas García, Víctor Eduardo (IE Revista de Investigación Educativa de la REDIECH, 2021)
The Internet is home to several texts on pseudo-therapies, but they do not have scientific evidence, and it is here where psychologists in training must have the ability to analyze the sources of knowledge, which can be related to the epistemological beliefs of each student. The aim of the present study was to analyze the arguments of psychology students when reviewing Internet texts on pseudo-therapies and to identify their epistemological beliefs. It is a cross-sectional, case study, whose sampling was non-probabilistic, by convenience, and consisted of eleven psychology students in the distance learning modality. They were given a script with which they had to analyze two texts on pseudo-therapies. The results were obtained by means of a descriptive quantitative analysis and also of co-occurrences. The findings show that the students tend to analyze the credibility of the texts based on the sources of information they cite, and they also found moderately sophisticated positions with respect to the contrast of sources and the notions of certainty provided by the evidence, although few of them showed links with previous knowledge of the discipline. The script proved to be a cognitive scaffold that favors a sophisticated level of text analysis in students.